2014
DOI: 10.1088/1612-2011/11/7/075101
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency generation in a short random fiber laser

Abstract: We demonstrate a high-efficiency random lasing in a 850-m span of a phosphosilicate fiber. Random distributed feedback owing to the Rayleigh backscattering in the fiber enables narrowband generation with the output power of up to 7.3 W at the Stokes wavelength λ S =1308 nm from 11 W of the pump power at λ P =1115 nm. The laser demonstrates unique generation efficiency. Near the generation threshold, more than 2 W of output power is generated from only 0.5W of pump power excess over the generation threshold. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 24 publications
(46 reference statements)
0
48
0
Order By: Relevance
“…However, the numerical study also revealed that in this configuration with short fiber length, the presence of a small reflection at fiber ends will significantly change the power distribution, lower the slope efficiency, reduce the second-order lasing threshold and appreciably deteriorate the power performance [26], [31]. Very recently, high power RFLs with short fiber length have been experimentally demonstrated [32], [33]. Vatnik et al utilized a 850 m long phosphosilicate fiber featuring a large Stokes shift and achieved 7.3 W of first-order random lasing operating at 1308 nm with 66% optical conversion efficiency [32].…”
mentioning
confidence: 94%
“…However, the numerical study also revealed that in this configuration with short fiber length, the presence of a small reflection at fiber ends will significantly change the power distribution, lower the slope efficiency, reduce the second-order lasing threshold and appreciably deteriorate the power performance [26], [31]. Very recently, high power RFLs with short fiber length have been experimentally demonstrated [32], [33]. Vatnik et al utilized a 850 m long phosphosilicate fiber featuring a large Stokes shift and achieved 7.3 W of first-order random lasing operating at 1308 nm with 66% optical conversion efficiency [32].…”
mentioning
confidence: 94%
“…Similar measurements could help to reveal hidden periodicity in the cavity-less lasers, such as random distributed feedback fibre lasers 25,26. Such lasers share many generation properties with conventional Raman fibre laser including possibility to polarized output 27, high-efficiency generation, 28 multi-wavelength 29 and tunable 30 generation. What is more important temporal dynamics of such lasers is defined as well by multiple turbulent like four-wave mixing processes 31, 32 which make their temporal radiation looking almost stochastic.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these advantages, attentions have been paid to their applications in fiber-optic sensing and communication [3]- [5]. Also, various aspects of RFL have been studied: RFL has been designed to be narrow bandwidth [6], multiwavelength [7], [8] wavelength-tunable [9], Manuscript high power [10]- [12] and generating high order Stokes waves [13], [14]. Besides, the concept of RFL can be further developed by using Brillouin gain instead of Raman gain [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some achievements about high power RFL were reported [10]- [12]. In Reference [10], near the 5.5W lasing threshold, more than 2W of output power is generated from only 0.5W of pump power excess over the threshold, and finally they obtained 7.3W output with 11W pump source, while the input-output curve is nonlinear. However, a linear output is generally preferred in most applications.…”
Section: Introductionmentioning
confidence: 99%